Visual Data Analysis of Time-Based Transport Optimizations - Barbu, Dragos C (IEEE computer graphics and applications, 2025)
This article proposes a novel approach to address the need for visual analysis tools in the transportation domain. Transportation planners require a tool to understand the interplay between vehicles, personnel, transported goods, and routes dynamically over time. Existing tools focus on map visualizations and are limited to animations when depicting changes over time in large amounts of data. We propose a design built from three views: absolute, relative, and topological, each showing a different data facet. We show how transport planners' trust in optimization algorithms can be achieved and how the same tool can be used to develop the optimization algorithm further